Research and Development (R&D) and Evaluation Research: A Comparative Analysis of Methodologies and Applications in Educational and Technological Innovation - Andi Syahrul; Khalifah Mustami; Syarifuddin Ondeng (Pustaka Digital Indonesia, 2025)
Education plays a crucial role in shaping individuals who are competent and prepared to face global challenges. One of the key components of education is the curriculum, which serves as a framework guiding the teaching and learning process. However, existing curricula often fail to respond adequately to the rapid pace of societal change and the evolving demands of the labor market. This study aims to explore the application of the Research and Development (R&D) approach as an evaluative method for curriculum development in education. The R&D approach enables evidence-based, responsive, and continuously evolving curriculum design through systematic stages such as needs analysis, prototype development, field testing, evaluation, and revision. The findings of this research indicate that implementing the R&D model enhances curriculum relevance, instructional effectiveness, and overall learning quality. Evaluation results demonstrate notable improvements in students’ critical thinking and collaboration skills, alongside high satisfaction levels among both teachers and learners. By integrating evaluation outcomes into the curriculum development cycle, educational programs can be continuously refined to align with the demands of the modern era and the workforce. This study concludes that the R&D approach significantly contributes to the creation of more adaptive, innovative, and effective curricula.